'˜ANOTHER VECTOR BORNE CHALLENGE TO COMBAT- ZIKA VIRUS OUTBREAKS' - Shoaib, Maria; Faraz, Ahmad; Ahmed, Syed Ahsanuddin (Journal of Ayub Medical College Abbottabad, 2016)
Zika virus is a single-stranded RNA virus of the Flaviviridae family. It is known to transmit to humans primarily through the bite of an infected Aedes species mosquito which is also known to carry dengue, chikungunya & yellow fever virus. Transmission is anthroponotic (human-to-vector-to-human) during outbreaks, Perinatally in utero, sexually and via infected blood transfusion. It is mild and self-limiting infection lasting for several days to a week. . However, it is suspected as a cause of Guillain Barre Syndrome. There is a teratogenic association of Zika virus causing congenital birth defects like microcephaly and neurologic abnormalities. Treatment is generally supportive and for symptomatic relief. No specific antiviral treatment or vaccine is yet available for Zika virus disease. It highlights importance of preventive public health measures at the community level and avoid travelling to the endemic areas.